Effective Prevention and Treatment of Substance Use Disorders for Racial and Ethnic Minorities - Guerrero, Erick; Khachikian, Tenie (IntechOpen, 2020)
Despite the significant burden of substance use disorders (SUD) across the world, SUD treatment systems face significant challenges to ensure immediate access to effective care. Prevention and treatment of SUDs is generally underfunded and its effectiveness to reduce substance use is frequently questioned. This book presents system level factors that may contribute to improving SUD prevention and treatment, particularly for underserved, and racial and ethnic minority populations. The authors provide theory-based approaches to prevention, as well as evidence-based spiritual, managerial, and leadership approaches to improve the effectiveness of SUD treatments. These approaches include modifiable system and organizational level factors that policy makers, healthcare administrators, treatment providers, and consumers can use to reduce the significant socio-economic burden of SUD on our society.